Does Intergovernmental Equalization Create Disincentives for Regional Infrastructural Development? - N. E. Barbashova (Финансы: теория и практика)
The subject of the research is the relationship between the amount of fiscal equalization grants and the length of transport routes in the regions. The study aims to test the hypothesis that the current formula for intergovernmental equalization creates disincentives for developing the road network in the regions. The relevance of the study is due to the fact that equalizing interterritorial inequality and regional infrastructural development are the most important goals of regional policy, whose instruments should not contradict. The current formula for distributing fiscal equalization grants contains a negative relationship between the length of transport routes in the regions and the amount of the transfer. That is, with an increase in the length of roads, the amount of grants to regions with initially low transport accessibility decreases. The author used the method of simulation modeling to quantify the reduction in grants to regions with low transport accessibility in the case of an increase in the length of roads in 2020 and to assess the potential impact of this decrease on the policy of regional authorities. As a result, the author revealed that while maintaining the current dynamics of road construction, an increase in the length of transport routes will lead to a decrease in the volume of grants to regions within 1%, which is insignificant regarding incentives. However, with an increase in the road network of hard-to-reach regions by one and a half times or more, this decrease may become critical. The work provides the estimate of the minimum additional fiscal revenue required to compensate for the lost income of the region with an increase in the length of transport routes. A further study may provide more details on the impact of the road industry development on the own revenues of regional budgets.